Ethnopharmacology of Psychotria: potential use of P. malayana Jack leaves as antidiabetic agent - Syed Mohamad, Sharifah Nurul Akilah; Khatib, Alfi; Mat So'ad, Siti Zaiton; Ahmed, Qamar Uddin; Ibrahim, Zalikha (IIUM Press, 2025)
This review provides a comprehensive exploration of the Psychotria species, a genus of plants known for their medicinal properties and traditional uses. The focus is on the species’ ethnomedicinal applications, their potential as an antidiabetic agent, the pharmacologically active antidiabetic compounds possessed, and their toxicological profiles. The escalating global prevalence of diabetes underscores the need for alternative therapeutic agents. The Psychotria species, with their antidiabetic properties, present a promising area of research. The traditional medicinal uses of the Psychotria species across various cultures are examined, providing valuable insights for the development of novel treatments. This review delves into the mechanisms through which these species exert their antidiabetic effects especially Psychotria malayana. The review discusses the pharmacologically active compounds unique to these species, which are of considerable interest for drug development in diabetes treatment. A summary of these studies and their implications is presented. Finally, the review addresses the toxicological studies on the Psychotria species, assessing their safety as therapeutic agents.